Prerequisites for Building an Omnichannel Strategy in the Food Chain - Vodenicharova, Maria (Research Papers, 2020)
The omnical approach can be used as a source of competitive advantage not only for electronics and clothing but also for food. The aim of this article is to examine the strategic advantages of the omnichannel supply chain approach and, on this basis, to outline the basic prerequisites for the introduction of an omnichannel strategy in the food supply chain in Bulgaria in order to adapt to consumer requirements. The survey methodology includes a closed-ended questionnaire designed in a way that allows us to assess the current state and expected changes over the next three years. The questions included in the questionnaire give an opportunity to study both the interconnections in the supply chain and the implementation of omnichannel in the food industry in Bulgaria. In the course of the study, a Y-matrix diagram was applied to show the relationship between customer requirements and metrics for internal processes and delivery channels. Still missing research omnichannel in the food industry in Bulgaria, which reveals the innovative nature of the research. In conclusion, it can be summarized that the introduction of an omnichannel strategy in the Bulgarian food industry is needed, which will strengthen consumer loyalty and producers will gain competitive advantages.
Keywords: Omnichannel; Food industry; Supply chains